A systematic review of long-term cardiotoxic effects of treatment in survivors of childhood acute lymphoblastic leukemia - Paige Johnson; Ellie Whitney; Coleton Evans; Donald Beam (Molecular and Cellular Pediatrics)
Abstract As progress in medical interventions for childhood cancer advances, the number of survivors of childhood acute lymphoblastic leukemia (ALL) is rising. Presently, the overall survival rate exceeds 90% over a five-year period. With this upward trend in survival rates, there’s a pressing necessity to investigate the enduring impacts of childhood cancer treatment. This systematic literature review focuses on the various long term cardiotoxic effects as a result of these treatments. The authors conducted a systematic review to identify studies that evaluated long-term cardiotoxic effects after anthracycline treatments among survivors of childhood ALL via PubMed search engine. Studies were included if ALL survivors were < 21 years old at the time of ALL diagnosis, an average of > 5 years post diagnosis and/or > 120 weeks post completion of consolidation therapy, compared with a healthy control population, and in remission during the assessment. Compared to matched control populations, survivors of childhood ALL had significantly higher rates of diastolic dysfunction and congestive heart failure. Additionally, female sex, younger age at diagnosis, and higher total dosing of anthracyclines administered during treatment led to significantly higher measures of cardiotoxicity. This study underscores the long-term cardiotoxic effects in ALL survivors, primarily linked to anthracycline use. Inconsistent detection of diastolic dysfunction via conventional echocardiogram necessitates regular monitoring of subclinical markers to prevent premature cardiac aging and heart failure. Future research should prioritize longitudinal studies to assess cardiotoxic effects throughout adult ALL survivors’ lifetimes, aiming to establish comprehensive follow-up guidelines.